Shadow Prices for Measures of Effectiveness, II: General Model - Robinson, Stephen M. (Operations Research, 1993)
This is the second of a pair of papers describing a two-sided game model of combat. In this paper, each side attempts to develop a force structure attaining the maximum of a prescribed merit function, subject to certain constraints expressed by a set of prescribed measures of effectiveness. These measures can be different for the two sides: furthermore, those of each side can depend on the other side's actions. A solution of the model is a generalized Nash equilibrium of this game, and such a solution also yields shadow prices that reveal the cost in merit paid by each side for requiring the specified level of performance on each measure of effectiveness. The first paper examines a special case in which the model has a linear structure, and shows that in a restricted case the shadow prices produced by that model are the classical eigenvalue weights familiar from Lanchester theory.